The construction process of strip footing for 465 units single storey house / Mohammad Nazirul Mubin Mohd Rasfan - Mohd Rasfan, Mohammad Nazirul Mubin (Universiti Teknologi MARA, Perak, 2022)
Substructure is one of the important things to be considered in construction process. Therefore, this report will discuss about substructure works based on Energiser Enterprise Sdn. Bhd. Specification. This report is conducted at Cadangan Pembangunan Secara Usahasama Program Khas Perumahan Perwira Negeri Perak (PKPPNP) Di Atas Lot 11523, Lot 11530 Dan Sebahagian Lot 10940 (Tanah Kerajaan), Mukim Bota, Daerah Perak Tengah, Perak Darul Ridzuan. The objective of this report is to study the construction method of strip footing. This report focused on all works related to concreting works and all the machineries and equipment used. This report also looks at the problems occurred during construction and their solutions. The strength of substructure is important for long term to make sure the building structure does not collapse, and all the load is properly distributed to the ground.